Nature and environment in Brazilian cordel literature - Nogueira, Carlos (Revista Vozes dos Vales: Publicações Acadêmicas, 2025)
In this article we approach the ecological thought in the Brazilian cordel, which, by relating areas like nature, environment, religion, technique, science, teaching, citizenship, and the denouncing of inequalities and injustices against people, living and non-living beings, has already configured a cycle that the Brazilian School has been giving more and more attention to.
Keywords: Portuguese language; Brazilian cordel literature; nature; environment; ecology